The Development of Accounting Information System Flowcharts and Document Techniques of PT. Indostar Building Material Focusing on Revenue Cycle - Andrianus, Eldon Darmatatya; Sukoharsono, Eko Ganis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The objective of this study is to analyse AIS of PT. Indostar Building Material (IBM) in terms of the sales division and provide the new design of accounting system in order to minimize the number of threats in PT. IBM. In spite of getting a deep understanding to the AIS of PT. IBM, therefore Content Analysis was implemented in narrative way. After analysing the revenue cycle in PT. IBM, it is found that there are ineffective and inefficiency in the system. Hence, a new and applicable design of the AIS in terms of the sales division is presented in this study. Keyword: Accounting Information Systemn, Financial performance, Segregation of duties, Revenue cycle